Marketing Transformation through Social Media: Implications for Business Growth and HR Performance Efficiency - Sulaeman, Moh. Muklis; Alista, Mery Nur; Nizar, Muhammad Rifqi Alfian; Alvianto, Victor; Prembayun, Sekar Dewi (PT. LITERASI SAINS NUSANTARA, 2024)
In today's digital era, social media has become one of the main tools in marketing strategy. Social media has changed the way consumers seek information, make decisions, and interact with brands. Consumers are now more likely to seek recommendations from friends or online reviews before buying a product or service. This research aims to comprehensively examine how marketing transformation through social media affects business growth and the efficiency of Human Resources (HR) performance in the company. This research uses a literature review method with a qualitative approach and descriptive analysis. Data is taken from articles available on Google Scholar in the 2015-2024 timeframe. The study results show that the transformation of marketing through social media has brought significant changes in the way companies interact with customers and promote their products. By leveraging platforms such as Facebook, Instagram, Twitter, and LinkedIn, companies can increase their reach, improve interaction with audiences, and optimise their operational efficiency.